Leigh syndrome in an infant: autopsy and histopathology findings - Arushi Gahlot Saini (University of São Paulo, 2021)
Leigh syndrome is an inherited neurodegenerative disorder of infancy that typically manifests between 3 and 12 months of age. The common neurological manifestations are developmental delay or regression, progressive cognitive decline, dystonia, ataxia, brainstem dysfunction, epileptic seizures, and respiratory dysfunction. Although the disorder is clinically and genetically heterogeneous, the histopathological and radiological features characteristically show focal and bilaterally symmetrical, necrotic lesions in the basal ganglia and brainstem. The syndrome has a characteristic histopathological signature that helps in clinching the diagnosis. We discuss these unique findings on autopsy and radiology in a young infant who succumbed to a subacute, progressive neurological illness suggestive of Leigh syndrome. Our case highlights that Leigh syndrome should be considered in the differential diagnosis of infantile-onset, subacute neuroregression with dystonia and seizures, a high anion gap metabolic acidosis, normal ketones, elevated lactates in blood, brain, and urine, and bilateral basal ganglia involvement.